Myocardial substrate metabolism in obesity. - Rider, O; Cox, P; Tyler, D; Clarke, K; Neubauer, S (2013)
Obesity is linked to a wide variety of cardiac changes, from subclinical diastolic dysfunction to end-stage systolic heart failure. Obesity causes changes in cardiac metabolism, which make ATP production and utilization less efficient, producing functional consequences that are linked to the increased rate of heart failure in this population. As a result of the increases in circulating fatty acids and insulin resistance that accompanies excess fat storage, several of the proteins and genes that are responsible for fatty acid uptake and metabolism are upregulated, and the metabolic machinery responsible for glucose utilization and oxidation are inhibited. The resultant increase in fatty acid metabolism, and the inherent alterations in the proteins of the electron transport chain used to create the gradient needed to drive mitochondrial ATP production, results in a decrease in efficiency of cardiac work and a relative increase in oxygen usage. These changes in cardiac mitochondrial metabolism are potential therapeutic targets for the treatment and prevention of obesity-related heart failure.